Learning English through nursery rhymes: teachers’ perspective / Geraldine John Philip De Mello … [et al.] - De Mello, Geraldine John Philip; Arumugam, Nalini; Hussin @ Ma’Mor, Misyana Susanti; Ibrahim, Mohammad Nor Afandi; Omar, Nur Hidayatulshima (Akademi Pengajian Bahasa, 2021)
Nursery rhymes play an important role in young children as they help develop an ear for learning the English language. This study aims to seek the encouragement of the pre-schoolers to learn vocabulary skills using nursery rhymes and to help them learn English spelling through the lyrics and animation of the rhymes. Additionally, pre-schoolers might enhance grammar knowledge through the arrangement of the lyrics. The role of using nursery rhymes in the language learning process has thoroughly been recognized since it helps teachers to put the learners in a motivating learning environment. Furthermore, it will encourage them to have more interaction while listening to the song and slowly share their thoughts with the help of their peers as well as the teacher. The study employed a survey design among 48 kindergarten teachers to collect data using a Google link form. The preliminary findings indicate that the majority of the preschool teachers agree that nursery rhymes should be used in the teaching of English while some disagree. Additionally, a large percentage find that the learners will also learn to use grammar and improve their vocabulary through nursery rhymes. This study affirms that the use of nursery rhymes can significantly enhance the awareness of learning vocabulary and grammar among the leaners at preschool. This research has significant pedagogical implications and developments on the role of using nursery rhymes to teach English as the learners will be motivated and they will be encouraged to be more interactive while listening to the nursery rhymes.